2011
DOI: 10.1136/ard.2010.139667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of etanercept versus sulfasalazine in early axial spondyloarthritis on active inflammatory lesions as detected by whole-body MRI (ESTHER): a 48-week randomised controlled trial

Abstract: PurposeTo evaluate the potential of etanercept versus sulfasalazine to reduce active inflammatory lesions on whole-body MRI in active axial spondyloarthritis with a symptom duration of less than 5 years.MethodsPatients were randomly assigned to etanercept (n=40) or sulfasalazine (n=36) treatment over 48 weeks. All patients showed active inflammatory lesions (bone marrow oedema) on MRI in either the sacroiliac joints or the spine. MRI was performed at weeks 0, 24 and 48 and was scored for active inflammatory le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
172
4
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(191 citation statements)
references
References 47 publications
7
172
4
8
Order By: Relevance
“…Recently, several studies of anti-TNF therapy have been conducted in nonradiographic axial SpA, with results suggesting that these agents have efficacy similar to that seen in radiographic axial SpA (15)(16)(17)(18)(19)(20). However, to date the number of large well-controlled studies of treatment with anti-TNF or other biologic agents in nonradiographic axial SpA, including populations of patients satisfying current ASAS criteria for nonradiographic axial SpA, is limited.…”
mentioning
confidence: 99%
“…Recently, several studies of anti-TNF therapy have been conducted in nonradiographic axial SpA, with results suggesting that these agents have efficacy similar to that seen in radiographic axial SpA (15)(16)(17)(18)(19)(20). However, to date the number of large well-controlled studies of treatment with anti-TNF or other biologic agents in nonradiographic axial SpA, including populations of patients satisfying current ASAS criteria for nonradiographic axial SpA, is limited.…”
mentioning
confidence: 99%
“…The anterior sacroiliac ligament (black arrows) gradually blends with the periosteum of the ilium and is therefore considered an enthesis (discontinuity due to cutting artifact). rigorous therapeutic regimen [11]. The positive likelihood ratio of MRI of the sacroiliac joints (SIJs) is as high as that of the HLA-B27 blood test [6].…”
mentioning
confidence: 99%
“…However, pre-radiographic axial SpA patients had lower levels of C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) and were better concerning function and metrology [29]. Further, clinical trials have shown that early axial SpA patients derive significant clinical benefits from TNFα blockade, which are associated with regression of spinal inflammation on MRI [30][31][32]. These observations have been incorporated in the 2010 updated ASAS recommendations for the use of anti-TNFα agents in SpA.…”
mentioning
confidence: 99%